Comparative Assessment of Intelligence Quotient among Children Living in High and Low Fluoride Areas of Kutch, India-a Pilot Study. - Ramesh Nagarajappa; Piyush Pujara; Archana J Sharda; Kailash Asawa; Mridula Tak; Pankaj Aapaliya; Nikhil Bhanushali (Tehran University of Medical Sciences, 2013)
Long-term ingestion of large amounts of fluoride can lead to potentially severe skeletal problems and neurological consequences. The study was conducted to assess and compare intelligence quotient of children living in high and low fluoride areas in Kutch, Gujarat, India.A cross-sectional descriptive survey was conducted among 100 school children aged 8 to 10 years, living in Kutch District, Gujarat, India during July 2012. Mundra (2.4 to 3.5 mg/L) and Bhuj (0.5mg/L) were the two villages randomly selected to represent the high and low water fluoride areas respectively. Seguin Form Board Test was used to assess the intelligence quotient (IQ) level of children. Descriptive statistics and independent sample t-test was used for analysis.Mean scores for average, shortest and total timing category were found to be significantly higher (P0.05).Chronic exposure to high levels of fluoride in water was observed to be associated with lower intelligence quotient.